2006
DOI: 10.1124/mol.105.019984
|View full text |Cite
|
Sign up to set email alerts
|

Differential Regulation of the Cell-Surface Targeting and Function of β- and α1-Adrenergic Receptors by Rab1 GTPase in Cardiac Myocytes

Abstract: The molecular mechanism underlying the export from the endoplasmic reticulum (ER) to the cell surface and its role in the regulation of signaling of adrenergic receptors (ARs) remain largely unknown. In this report, we determined the role of Rab1, a Ras-like GTPase that coordinates protein transport specifically from the ER to the Golgi, in the cell surface targeting and function of endogenous ␤-and ␣ 1 -ARs in neonatal rat ventricular myocytes. Adenovirus-driven expression of Rab1 into myocytes selectively in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
53
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
4

Relationship

7
3

Authors

Journals

citations
Cited by 51 publications
(54 citation statements)
references
References 38 publications
1
53
0
Order By: Relevance
“…In this context, another IC protein, Rab1, has also been implicated in the intracellular trafficking of some GPCRs to the plasma membrane. Experiments inhibiting rab1 expression led to the characterization of rab1-dependent and -independent pathways from the ER to the plasma membrane depending on the GPCR studied (Wu et al, 2003;Filipeanu et al, 2006). Similarly, concerning another family of receptors, the regulation of a nicotinic acetylcholine receptor subtype trafficking has been recently described in Caenorhabditis elegans, revealing that its traffic depended on UNC-50, an endoplasmic reticulum-Golgi intermediate compartment (ERGIC)-associated protein (Eimer et al, 2007).…”
Section: Yif1b Is Implicated In 5-ht 1a Trafficking In Dendritesmentioning
confidence: 99%
“…In this context, another IC protein, Rab1, has also been implicated in the intracellular trafficking of some GPCRs to the plasma membrane. Experiments inhibiting rab1 expression led to the characterization of rab1-dependent and -independent pathways from the ER to the plasma membrane depending on the GPCR studied (Wu et al, 2003;Filipeanu et al, 2006). Similarly, concerning another family of receptors, the regulation of a nicotinic acetylcholine receptor subtype trafficking has been recently described in Caenorhabditis elegans, revealing that its traffic depended on UNC-50, an endoplasmic reticulum-Golgi intermediate compartment (ERGIC)-associated protein (Eimer et al, 2007).…”
Section: Yif1b Is Implicated In 5-ht 1a Trafficking In Dendritesmentioning
confidence: 99%
“…Moreover, several studies have shown that manipulation of components involved in the ER export machinery may also selectively influence receptor PME and function. This is the case of the small GTPase Rab1 protein, a member of the Rab GTPase family of proteins (Martinez and Goud 1998); Rab1 is specifically localized in the ER and Golgi apparatus and regulates anterograde transport from the ER to and through the Golgi of several proteins (Yoo et al, 2002;Wu et al, 2003;Filipeanu et al, 2004Filipeanu et al, , 2006. Attenuation of Rab1 function by expressing DN Rab1 mutants or siRNA-mediated depletion of endogenous Rab1 inhibited cell surface expression of a number of endogenous GPCRs (including the angiotensin-1 receptor and the ␤ 2 -adrenergic receptor) and promoted their accumulation in the ER and the Golgi (Wu et al, 2003;Filipeanu et al, 2004).…”
mentioning
confidence: 99%
“…As an initial approach to elucidate the mechanism of nascent GPCR targeting to the cell surface, we have determined the role of Sar1 and several Rab GTPases in regulating cell surface transport of representative GPCRs, including the angiotensin II and adrenergic receptor (AR) subfamilies (Wu et al, 2003;Filipeanu et al, 2004;Filipeanu et al, 2006;Dong et al, 2008;Zhang et al, 2009). Our studies indicate that the cell surface transport of different GPCRs may be mediated through distinct pathways and suggest a novel pathway mediating ␣ 2B -AR traffic from the ER to the Golgi apparatus (Wu et al, 2003).…”
mentioning
confidence: 99%